STRATEGY, STRUCTURE AND PERFORMANCE IN INDIA - PILLANIA, Rajesh K. (Journal of Advanced Research in Law and Economics; Vol 3 No 1(5) (2012): Volume III, Issue 1(5), Summer 2012, 2017)
Indian economy is on a growth trajectory and one study after another is projecting India among the leading economies of future. The role and significance of India in the global economy is continuously increasing. Following the seminar work of Chandler, strategy and structure research has made a lot of progress and is one of the major research issues in strategy. This paper studies the strategy and structure in the top 100 companies in India. We find that more companies are focusing on it as they have started facing competition and also started reaping the fruits of this aspect.